Apruma o corpo e bata continência como homem: a vida laboral de homossexuais no Corpo de Bombeiros de Minas Gerais - Leonardo Tadeu dos Santos (2019)
In this study, I sought to discuss the sexuality of gay firemen, highlighting their statements and their true effects. More specifically the statements and truths surrounding the masculinity and heteronormativity- or not- of these subjects in their wwork contexto. Thus, my intention was to bring and bring up the most varied discuourses that permeate the question of masculinity and heteronormativity in the life of these firemen: discourses of work, Family, religion, politics. The Minas Gerais Military Fire Brigade (CBMMG) has a history of 106 years, full of challenges and achievements and parades as one of the most admired public institutions and respected by civil society. In this way. I tried to show how, throughout its history, the fire departamento of Minas Gerais has built a discourse focused on the valorisation and creatrion of an image of firemen and heteronormativity. For this, in the theoretical construction I based on the writings of Michel Foucault using the concepts of power, discourses and their effects on organizations. The construction of the methodology, also based on the writings of the philosopher Michel Foucault, sought to constructo na astisanal methodology in which I allowwed the search and mining of the date that i thought were more importante to understand the proposed theme. The result is a tangle of discourses, many which are disconnected, that (re)consruct and (re)affirm a mascular, heteronormative and heroic image of firefighters.